2018
DOI: 10.1002/sres.2540
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Skills for the World of Work in the Digital Age

Abstract: The skills that small and medium-sized enterprises will need in the near future are an essential research topic that has not yet been appropriately addressed. The current paper aims to fill this gap in the literature. Explicitly, the study aimed to identify the critical skills for organizations and the disruptive technological skills. To this end, a literature review was conducted, and an online survey explored the main critical skills for the future and the disruptive technological skills contributing to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 16 publications
2
37
0
3
Order By: Relevance
“…SMEs need a blend of hard aptitudes, for instance, the capacity to utilize the innovation and break down higher volumes of information, just as the delicate abilities, for instance, tackling ineffectively organized issues, grasping change, ideation, and opportunity acknowledgment [48], [49]. Surviving exploration shows that workers' information and aptitudes, including basic reasoning, critical thinking capacities, and the capacity to team up in systems are on the whole fundamental to digitalization [49]. Worker aptitudes are pivotal to changing an organization's IT scene [49], [50].…”
Section: Individual Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…SMEs need a blend of hard aptitudes, for instance, the capacity to utilize the innovation and break down higher volumes of information, just as the delicate abilities, for instance, tackling ineffectively organized issues, grasping change, ideation, and opportunity acknowledgment [48], [49]. Surviving exploration shows that workers' information and aptitudes, including basic reasoning, critical thinking capacities, and the capacity to team up in systems are on the whole fundamental to digitalization [49]. Worker aptitudes are pivotal to changing an organization's IT scene [49], [50].…”
Section: Individual Skillmentioning
confidence: 99%
“…Surviving exploration shows that workers' information and aptitudes, including basic reasoning, critical thinking capacities, and the capacity to team up in systems are on the whole fundamental to digitalization [49]. Worker aptitudes are pivotal to changing an organization's IT scene [49], [50]. It can in this way be hypothesized: H2: Employee skills positively relate to the digital marketing of MSMEs.…”
Section: Individual Skillmentioning
confidence: 99%
“…A continuación, se abordarán aspectos clave de la llamada "transformación digital" en las organizaciones empresariales y sus efectos sobre las personas que las integran. Esta circunstancia reclama nuevas maneras de dirigir y organizarse, así como habilidades y competencias específicas en el personal que conforma la compañía a lo largo de toda su cadena de valor (Cascio y Montealegre, 2016); lo que aumenta la presión por disponer y desarrollar el talento adecuado con el que poder competir en un mercado cada vez más dinámico y exigente (Sousa y Wilks, 2018).…”
Section: La Transformación En Constante Transformaciónunclassified
“…Esta circunstancia, única respecto al resto de generaciones, ha permitido que desarrollen una serie de habilidades y competencias entre las que se destacan el hecho de sentirse cómodos recopilando e integrando información de diferentes fuentes de información de una manera ágil (Francis y Hoefel, 2018), una gran capacidad de adaptación (Maioli, 2017), una mentalidad emprendedora capaz de promover nuevas ideas (Schroth, 2019) y una mayor actitud colaborativa de carácter global (Issa e Isaias, 2016), entre otras. Todas ellas se consideran competencias críticas para las organizaciones en la era digital (Sousa y Wilks, 2018); lo que confirma lo mucho que estas generaciones pueden aportar a la transformación.…”
Section: La Digitalización No Es Tecnológicaunclassified
“…Sousa and Rocha [33] have found that the set of necessary competences of employees is changing under the influence of the effects of the Internet of things, cloud technologies, large data, mobile technologies, artificial intelligence and robotics. Sousa and Wilks [34] concluded in their study that the skills of critical thinking, adaptation, network collaboration and creativity skills will be essential in today's business environment.…”
Section: Literature Reviewmentioning
confidence: 99%